2020
DOI: 10.21203/rs.3.rs-45906/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends and outcomes of blunt renal trauma management: A nationwide cohort study in Japan

Abstract: Background There is a paucity of information for predicting patient outcomes other than the American Association for the Surgery of Trauma (AAST) renal injury scale. The aim of this study was to evaluate the association between the patient characteristics and outcomes of patients with blunt renal trauma using a nationwide database in Japan. Methods We performed a retrospective analysis of the Japan Trauma Data Bank (JTDB) from 2004 to 2018. We identified patients with blunt renal trauma by AIS codes converte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, case reports of severe isolated kidney injuries have been reported, 16 as well as retrospective studies suggesting isolated renal injuries are more common in younger children. 17 In this context, the finding that isolated BRT is independently associated with urine leaks in children indicates that this population may benefit from greater clinical suspicion, earlier diagnostic evaluation, and closer monitoring. Specifically, although it did not meet statistical significance, our study showed that children developing urine leaks had a lower ISS (n = 17) relative to those who did not (n = 24), which likely reflects isolated BRT having more frequent urine leaks yet lower ISS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, case reports of severe isolated kidney injuries have been reported, 16 as well as retrospective studies suggesting isolated renal injuries are more common in younger children. 17 In this context, the finding that isolated BRT is independently associated with urine leaks in children indicates that this population may benefit from greater clinical suspicion, earlier diagnostic evaluation, and closer monitoring. Specifically, although it did not meet statistical significance, our study showed that children developing urine leaks had a lower ISS (n = 17) relative to those who did not (n = 24), which likely reflects isolated BRT having more frequent urine leaks yet lower ISS.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other identified risk factors, isolated BRT is rarer and often presumed a more minor injury, 14,15 leading potentially to less timely evaluation. Nonetheless, case reports of severe isolated kidney injuries have been reported, 16 as well as retrospective studies suggesting isolated renal injuries are more common in younger children 17 . In this context, the finding that isolated BRT is independently associated with urine leaks in children indicates that this population may benefit from greater clinical suspicion, earlier diagnostic evaluation, and closer monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal injuries are more common in children due to their flexible rib cage and less developed abdominal muscles [30]. Previous studies demonstrated that severe sports-related abdominal injuries, such as renal injury, are more likely to occur as in isolated injury in children [31,32]. A previous study that analyzed an international trauma database reported that head, chest, spinal and pelvic injuries were common in major trauma in winter sports [24].…”
Section: Discussionmentioning
confidence: 99%